Indian Public Health Students' Perspectives on Global Health Education - Sawleshwarkar, Shailendra; Zodpey, Sanjay P.; Negin, Joel (Frontiers in Public Health, 2021)
Global health discipline is of increasing interest for educators and students in public health across the world. Public health education is recently gaining momentum in India, but global health is still at an embryonic stage. Value of students as stakeholders in curriculum development is increasingly recognized but literature about perspectives of public health students regarding global health education is limited. This study aimed to explore Indian public health students' perspectives about global health education and to provide platform for the development of global health education framework for future public health professionals. This study involved a series of focus groups with students and sought to understand perceptions about global health and global health education framework. We recruited public health students at three institutes across India for focus group discussions. Focus groups questions covered current understanding of global health, opinions regarding global health education for public health curriculum and the relevance of global health competency domains for future employment. Recordings were transcribed verbatim and the transcripts were read along with field notes and then analyzed thematically. A total of 36 students participated in four focus groups. There was a general recognition that global health is transnational and that a global outlook is now essential. But there were concerns regarding local and global priorities in public health. Global health was regarded as being wider than public health by some, but others viewed public health being the umbrella term with global health as a specialization. Global health competencies were viewed as a “step up” from the public health competencies but core public health competencies were considered essential. International experiences and use of technology were key themes for delivery of global health education. Employability and career progression for global health graduates were of concern for many participants. This study provides insight into the student perspectives regarding global health education for public health programs in India. Clear direction in terms of curriculum and its utility for career growth and employability as a global health professional needs to be established for global health education in India and other similar settings.